2005
DOI: 10.1111/j.1745-7254.2005.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of huperzine A on secretion of nerve growth factor in cultured rat cortical astrocytes and neurite outgrowth in rat PC12 cells

Abstract: Aim: To study the effects of huperzine A (HupA) on neuritogenic activity and the expression of nerve growth factor (NGF). Methods: After being treated with 10 µmol/L HupA, neurite outgrowth of PC12 cells was observed and counted under phase-contrast microscopy. Mitogenic activity was assayed by [ 3 H]thymidine incorporation. Cell cytotoxicity was evaluated by lactate dehydrogenase (LDH) release. AChE activity, mRNA and protein expression were measured by the Ellman's method, RT-PCR, and Western blot, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 32 publications
1
22
1
1
Order By: Relevance
“…In contrast, BDNF and NGF levels did not show any significant changes after the fluctuant inhibition of AChE in HT-treated mice. These results differ from previous studies, which concluded that AChE inhibitors increase neurotrophic factors levels (18,(20)(21)(22). Regarding the contradictory results, it must be noted that the neurotrophic factor levels in the previous studies were measured immediately (4 to 24 h) after administration of AChE inhibitors.…”
contrasting
confidence: 55%
“…In contrast, BDNF and NGF levels did not show any significant changes after the fluctuant inhibition of AChE in HT-treated mice. These results differ from previous studies, which concluded that AChE inhibitors increase neurotrophic factors levels (18,(20)(21)(22). Regarding the contradictory results, it must be noted that the neurotrophic factor levels in the previous studies were measured immediately (4 to 24 h) after administration of AChE inhibitors.…”
contrasting
confidence: 55%
“…Accumulating evidence indicates that AChE may influence neurite outgrowth through a non-catalytic mechanism [138] . Hence, the effect of HupA on neurite outgrowth may be associated with the level of AChE expression [139] . Neurotrophic factors such as NGF not only promote the survival of responsive neurons but also protect them from oxidative injury.…”
Section: Effects On Nerve Growth Factormentioning
confidence: 99%
“…In line with this observation, huperzine A administration was found to enhance the expression and secretion of NGF, as well as increase p75NTR mRNA in primary astrocytes [12] , enhance the non-amyloidogenic pathway by increasing the levels of sAPPα [13] possibly associated with M1 muscarinic ACh receptor mediated pathway [14][15][16] , and reduce the hypoxia ischemiatriggered inflammatory response through α7 nicotinic ACh receptor [17][18][19] . Since previous study has proven that huperzine A had no direct effect on the amplitude or kinetics of nAChRs activation [20] , above cholinergic system-associated beneficial effects of huperzine A administration may mainly act through the enhancement of synaptic ACh level.…”
Section: Multifaceted Pharmacological Effects Of Huperzine A: Cholinementioning
confidence: 69%